D-(π-A)3 type low bandgap star-shaped fused-ring electron acceptor with alkoxy-substituted thiophene as π-bridge. (June 2021) - Wang, Tong; Wang, Weijie; Wu, Xiaofu; Tong, Hui; Wang, Lixiang
Abstract: As a strong electron-donating π-bridge, alkoxy-substituted thiophene has been widely used in low bandgap fused-ring electron acceptors (FREAs), while its application in star-shaped FREAs has never been explored. Herein, a donor-(π-acceptor)3 type low bandgap star-shaped FREA with ethylhexyloxy-thiophene π-bridge, namely TITT-OT-ICF, is synthesized. The enhanced intramolecular charge transfer of TITT-OT-ICF leads to a high-lying HOMO level, and thus a narrower optical band gap of 1.47 eV relative to its counterpart TITT-T-ICF with ethylhexyl-thiophene as π-bridge (1.61 eV). When blending with a wide bandgap polymer donor PBDB-T, EQE spectrum of TITT-OT–ICF–based organic solar cell (OSC) device is extended to 880 nm, while that of PBDB-T: TITT-T–ICF–based device is limited to 800 nm. In spite of similar phase morphologies in both active layers, the broader photoresponse of PBDB-T: TITT-OT–ICF–based device leads to a higher short-circuit current density ( J SC ) of 16.95 mA cm −2, yielding a higher power conversion efficiency (PCE) of 8.23% in comparison with PBDB-T: TITT-T–ICF–based device ( J SC = 14.33 mA cm −2, PCE = 7.53%). These results demonstrate a rational design of low bandgap star-shaped FREAs based on alkoxy-substituted thiophene as the π-bridge for achieving relatively high J SC and PCE. Highlights: Star-shaped FREA TITT-OT-ICF with alkoxy-thiophene π-bridge is synthesized. TITT-OT-ICF has lower E g opt (1.47 eV) than TITT-T-ICF with alkyl-thiophene (1.61 eV). The EQE spectrum of TITT-OT–ICF–based OSC device can be extended from 300 to 880 nm. TITT-OT–ICF–based device shows a better PCE of 8.23% with a J SC of 16.95 mA cm -2 .